Coexistence of a novel STRN-ALK, NBEA-ALK double-fusion in an ovarian malignant mesothelioma patient: a case report and review - Wu, Xiao; Wang, Qi; Xu, Xiaohu (Frontiers in Oncology, 2023)
Primary ovarian mesothelioma (POM) is a rare malignant tumor with poor prognosis. Although anaplastic lymphoma kinase gene (ALK) double-fusion partners have been found in various tumors, it is rarely reported in mesothelioma. In this article, we describe the coexistence of a novel STRN-ALK, neurobeachin (NBEA)-ALK double-fusion in a patient with primary ovarian mesothelioma. A 30-year-old woman was found to have pelvic masses for more than a year. Color Doppler ultrasound showed mixed mass in the left ovary and multiple solid masses in the right ovary. the patient underwent laparoscopic surgery, including total hysterectomy, bilateral salpingo-oopherectomy, pelvic lymph node and abdominal aortic lymph node resection, omentum resection and abdominal focus resection. Pathologic examination revealed bilateral ovarian malignant mesothelioma and no evidence of malignancy in the resected bilateral round/broad ligaments, bilateral parametrial tissues, vaginal stump, bilateral fallopian tubes, pelvic and paraaortic lymph nodes. Immunohistochemistry showed that it was positive for Calretinin, VIM, WT1, PAX8, mesothelin, CK5/6, PCK, CK7, MLH1, PMS2, MSH2, MSH6, weakly positive for BAP1, while being negative for Napsin A, P504S, CEA, D2-40, GATA3. The sequencing analysis identified STRN-ALK (intron3:intron19) and NBEA-ALK (intron1:intron16) double-ALK fusion. To the best of our knowledge, this is the first report that a novel NBEA-ALK and EML4-ALK coexist in one patient with POM. The patient has completed 6 cycles of continuous chemotherapy and is in stable condition. Whether ALK inhibitors can bring promising benefits to POM patients in the future deserves further study.